IMPLEMENTATION OF MULTIMEDIA-BASED LEARNING MEDIA TO STIMULATE THE ABILITY TO RECOGNIZE GEOMETRY CONCEPTS IN KINDERGARTEN FKIP UNSYIAH - Rossiana Br Ginting; Diana; Helnita; Satria Prayudi (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Introducing geometric shapes in early childhood is the ability of children to recognize, point, mention and collect objects around based on geometric shapes by using geometry game applications on android. Introducing geometric shapes in early childhood starts from building geometric concepts, namely by identifying the characteristics of geometric shapes. Before identifying geometric shapes, in children's cognitive development according to Bloom's theory there are six levels of processes in thinking, including knowing, understanding, applying, analyzing, evaluating, and creating. The purpose that will be carried out in this study is at the level of the ability to know, recognize, and apply with geometry game applications that have been downloaded on the playstore on Android. In this study, researchers wanted to see how children's knowledge about recognizing geometric shapes and how to improve the ability to recognize geometric shapes in children